STUDYING THE DEEP STRUCTURE IN THE SAIGON RIVER FAULT AREA BY THE MAGNETOTELLURIC METHOD - Hung, Luu Viet; Menvielle, Michel; Minh, Le Huy; Son, Vo Thanh; Thang, Nguyen Chien; Marquis, Guy; Trieu, Cao Dinh (Vietnam Journal of Earth Sciences, 2014)
This paper presents the magnetotelluric sounding results of Cu Chi - Ben Cat profile across the Saigon River fault. Results obtained by one-dimensional inversion of the data of a typical station located near the middle of the profile show that the geoelectric structure of the study area consists of three layers, in which the resistivities of the superficial and the underlying layers are relatively low compared with that of the intermediate layer. This geoelectric structure is then used to estimate the influence of the equatorial electrojet on the magnetotelluric measurements carried out in the region. Magnetotelluric forward problems were calculated and compared for cases of the present and the absent of the equatorial electrojet model. Results show that in the range of periods less than 0.7s, the apparent resistivity measured are not affected by the equatorial electrojet. Therefore, the apparent resistivity data measured in the period range less than 0.7s of all stations on the profile have been used for two-dimensional inversion to obtain geoelectric cross-section acrossing the Saigon River fault. The geoelectric cross-section down to a depth of 10km obtained by two-dimensional inversion shows a geoelectric structure consist of 3 layers: a low resistivity superficial layer, a resistive intermediate layer, and a low resistivity underlying layer. The superficial layer is clearly related to the sedimentary series. The intermediate layer may relate to the intrusive and consolidated rocks. The underlying layer may reflect conductive materials causing by high-temperature condition at depth. The interface between the intermediate and the underlying layers at around 3km depth corresponds probably to the crystalline basement. The low resistivity regions under the C4 and C2 stations may be related to the Duong Minh Chau - Dau Tieng - Can Gio and the Saigon River faults, correspondingly. References S. C. Constable, R. L. Parker, and C. G. Constable, 1987. Occam’ s inversion: A practical algorithm for generating smooth models from EM sounding data, Geophysics, 52, 289-300. H. Grandis, M. Menvielle, and M. Roussignol, 1999. Bayesian inversion with Markovchains-I. Themagnetotelluric one-dimensional case, Geophys. J. Int., 138, 757-768. Trương Quang Hảo, Lương Văn Trương, 2005. Xác định một vài thông số của dòng điện xích đạo ở Việt Nam, Tuyển tập báo cáo Hội nghị khoa học kỹ thuật địa vật lý Việt Nam lần thứ 4, 47-70. Trương Quang Hảo, 1997. Thành tựu nghiên cứu Vật lý Địa cầu 1987-1997. Trung tâm Khoa học Tự nhiên và Công nghệ Quốc Gia, viện Vật lý Địa cầu, Nxb. KHKT, 202-236. Nguyễn Ngọc Hoa (chủ biên), 1995. Bản đồ địa chất và khoáng sản Việt Nam, tỷ lệ 1:200.000, tờ C-48-XI, Thành phố Hồ Chí Minh, Cục Địa chất và Khoáng sản Việt Nam, Hà Nội. Đặng Văn Hưng, 1987. Tính chất của trường điện từ tự nhiên miền xích đạo từ và độ chính xác của của phương pháp MTS ở Việt Nam, Tạp chí các Khoa học về Trái Đất, T.9, 2, 61-66. A. G. Jones, 1992. Electrical conductivity of the continental lower crust, Continental lower crust, Edi. D. M. Fountain, R. J. Arculus and R. W. Kay, 81-143. S. K. Lee et al, 2009. MT2DinvMatlab-A program in MATLAB and FORTRAN for two-dimensional magnetotelluric inversion, Computers & Geosciences, 35, 1722-1734. Đỗ Văn Lĩnh (chủ biên), 2009. Báo cáo thuyết minh đề tài “Phân vùng nhỏ động đất khu vực thành phố Hồ Chí Minh”, Sở Khoa học và Công nghệ thành phố Hồ Chí Minh, 248tr. Lê Huy Minh, Nguyễn Văn Giảng, Nguyễn Trọng Vũ và Lại Cao Khiêm, 2004. Kết quả sơ bộ nghiên cứu cấu trúc sâu vùng đồng bằng Sông Cửu Long, Tuyển tập báo cáo Hội nghị Khoa học cơ bản, Thành phố Hồ Chí Minh 12/2004. Lê Huy Minh, Nguyễn Chiến Thắng, Lưu Việt Hùng, 2005. Kết quả đo sâu từ telua tuyến Chợ Gạo- Hóc Môn, Tuyển tập báo cáo Hội nghị Khoa học kỹ thuật Địa vật lý Việt Nam lần thứ 4, 149-161. Lê Huy Minh, Phạm Văn Ngọc, D. Boyer, Nguyễn Ngọc Thủy, Lê Trường Thanh, Ngô Văn Quân, G. Marquis, 2009. Nghiên cứu chi tiết cấu trúc đứt gãy Lai Châu - Điện Biên bằng phương pháp đo sâu từ tellur, Tạp chí Địa chất loạt A, 311, 11 -21. W. R. Peltier and J. F. Hermance, 1971. Magnetotelluric Fields of a Gaussian Electrojet, Canadian Journal of Earth Sciences, 8(3), 338-346. V. N. Pham, D. Boyer, T. K. T. Nguyen, and V. G. Nguyen, 1994. Deep ground-water investigation by combined VES/MTS methods near Ho Chi Minh City, Viet Nam, Ground water, 32, 4, 675-682. P. Tapponier et al., 1990. The Ailao Shan/Red River metamorphic belt: Tertiary left-lateral shear between Indochina and South China, Nature, 343, 431-437. Nguyễn Ngọc Thu, 2004. Xử lý tổng hợp tài liệu địa vật lý vùng thành phố Hồ Chí Minh, Luận án Tiến sĩ vật lý, Đại học Quốc Gia Tp. Hồ Chí Minh, 146tr. Cao Đình Triều, 2005. Trường địa vật lý và cấu trúc thạch quyển lãnh thổ Việt Nam. Nxb. KHKT, Hà Nội, 330tr. Cao Đình Triều, Phạm Huy Long, Đỗ Văn Lĩnh, Lê Văn Dũng, Cao Đình Trọng, 2013. Địa động lực hiện đại lãnh thổ Việt Nam. Nxb. Khoa học Tự nhiên và Công nghệ, 242tr. J. T. Weaver and A. K. Agarwal, 1993. Automatic 1-D inversion of magnetotelluric data by the method of modeling, Geophys. J. Int, 112, 115-123.